2001
DOI: 10.1149/1.1339864
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Characterization of Erbium-Doped TiO[sub 2] Xerogel Films Processed on Porous Anodic Alumina

Abstract: Titania films, doped with erbium, were fabricated on porous anodic alumina from a normalTifalse(OC2H5)4 precursor. The samples, subjected to thermal processing up to 1270 K, exhibited strong luminescence at 1.53 μm associated with 4I13/2→4I15/2 transitions of Er3+ ions in the TiO2 xerogel. The intensity of photoluminescence increased with the number of xerogel film depositions onto alumina. Secondary ion mass spectrometry analyses show that the pores of anodic alumina are filled by the xerogel after se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…The sol-gel materials have been investigated for various optical applications, such as anti-refractive coatings, planar optical waveguides, optical filters and optical sensors [2][3][4][5][6][7][8]. It has been demonstrated that silica, titania and silica-titania materials may be doped with rare-earth ions and organic dyes via the sol-gel techniques, the spin-top deposition [9] and the sonochemical method [10]. The sol-gel technology provides an excellent way of obtaining transparent and mechanically stable films, bulk glasses, powder and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel materials have been investigated for various optical applications, such as anti-refractive coatings, planar optical waveguides, optical filters and optical sensors [2][3][4][5][6][7][8]. It has been demonstrated that silica, titania and silica-titania materials may be doped with rare-earth ions and organic dyes via the sol-gel techniques, the spin-top deposition [9] and the sonochemical method [10]. The sol-gel technology provides an excellent way of obtaining transparent and mechanically stable films, bulk glasses, powder and fibers.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen in the insert that the xerogel layer processes also in the surface of PAA and the pores are still opened for further xerogel penetration inside. After 5-10 spin-on steps the full pore filling is approached [10] and planarization of PAA surface by xerogel occurs [11].…”
Section: Resultsmentioning
confidence: 99%
“…High-transparency of anodic alumina oxide on the one hand and strong optical anisotropy on the other hand may be the reasons of growing interest to exploit this material as a cage for light-emitting species. Filling the channels of the pores of anodic alumina films with silica [36][37][38], titania [23,[39][40][41][42], alumina [43][44][45] xerogels doped with lanthanide ions Er [37][38][39], Tb [23,38,44] and Eu [35,[40][41][42]45], organic dyes [46], semiconductor nanocrystals [47,48], polymers [ 49,50], quantum dots [51,52], and biological samples [53] was investigated, and strong luminescence of optically active species incorporated in voids of anodic alumina or, probably, in its walls [54,55] was reported.…”
Section: Porous Anodic Aluminamentioning
confidence: 99%
“…To investigate the spatial distribution of xerogel deposited onto PAA by spinning followed by thermal treatment, selected samples containing terbium-doped titania and alumina xerogels were examined by SIMS [37][38][39], transmission electron microscopy (TEM), SEM and energy distribution of X-ray (EDX) analyses [23,40,41]. After the first spin-on deposition of a sol followed by drying transmission electron micrographs revealed relatively dark, fine textured material of amorphous appearance at the base of the pore.…”
Section: Porous Anodic Aluminamentioning
confidence: 99%